PENGGUNAAN MEDIA PEMBELAJARAN POP UP BOOK UNTUK MENINGKATKAN PEMAHAMAN BELAJAR SISWA MI DALAM MENGELOMPOKKAN JENIS TUMBUHAN - Muhammad Kholil; NurFadilatun Nisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low concentration and interest in learning of students causes the results of student learning achievement to be less than optimal. This happens because of the lack of learning media used by teachers in delivering the material so that learning is less effective. In this case, the researcher wants to implement and test the Pop up book learning media to improve students' learning understanding so that students can understand the material easily, especially in the material "Grouping Plant Types. The approach used in this study is a qualitative approach with a descriptive research framework, in the form of a case study. Data collection techniques used are interviews, observations, and documentation. The results of the study showed that the Pop up book learning media proved to be feasible and categorized as very valid. This media has a significant influence that is successful in provoking students' concentration and interest in learning, as well as facilitating and improving students' learning understanding of the material presented. This can be proven by the existence of Pop up book learning media making students more active and enthusiastic in participating in learning in class.